Electromagnetic properties of the Delta(1232) and decuplet baryons in the self-consistent SU(3) chiral quark-soliton model - Tim Ledwig (2009)
We examine the electromagnetic properties of the Delta(1232) resonance within the self-consistent chiral quark-soliton model. In particular we present the Delta form factors of the vector-current GE0, GE2 and GM1 for a momentum-transfer range of $Q^{2} ≤ 1GeV^{2}$. We apply the symmetry-conserving quantization of the soliton and take 1/N_c rotational corrections into account. Values for the magnetic moments of all decuplet baryons as well as for the N-Delta transition are given. Special interest is also given to the electric quadrupole moment of the Delta.